34th AIAA Fluid Dynamics Conference and Exhibit 2004
DOI: 10.2514/6.2004-2246
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer Control for Hypersonic Airbreathing Vehicles

Abstract: Active and passive methods for tripping hypersonic boundary layers have been examined in NASA Langley Research Center wind tunnels using a Hyper-X model. This investigation assessed several concepts for forcing transition, including passive discrete roughness elements and active mass addition (or blowing), in the 20-Inch Mach 6 Air and the 31-Inch Mach 10 Air Tunnels. Heat transfer distributions obtained via phosphor thermography, shock system details, and surface streamline patterns were measured on a 0.333-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…al. 41 demonstrated that mass injection from discrete orifices could successfully induce boundary layer transition consistent with that observed with the more conventional protuberance-based discrete roughness. Stalmach et.…”
Section: Localized Ablatorssupporting
confidence: 53%
“…al. 41 demonstrated that mass injection from discrete orifices could successfully induce boundary layer transition consistent with that observed with the more conventional protuberance-based discrete roughness. Stalmach et.…”
Section: Localized Ablatorssupporting
confidence: 53%
“…The ratio of the plenum pressure to plate pressure is a relevant parameter in the current experiment. Berry et al 7 found that, for slot injection, the plenum pressure needed to be 25 times higher than the plate pressure to transition the flow to turbulence within 127 mm (5.0 in) of the slot. From the data shown in Fig.…”
Section: No Trip: Pressure Measurementsmentioning
confidence: 99%
“…The use of a slot for seeding (as opposed to the 4 pressure ports used in Reference 3) and the choice of a flowrate of 0.3 slpm was largely based on the work of Berry et al . 7 who studied blowing-induced transition on a Hyper-X forebody model. Berry et al found that, for a given flowrate of gas, injection from a spanwise slot was the least effective method and that a spanwise row of holes was the most effective method for tripping a boundary layer to transition to turbulence.…”
Section: A Test Articlementioning
confidence: 99%
“…4 In the X-43A work, schlieren flow visualization provided useful information about shock positions, although this information was path-averaged and turbulent flow structures were not identified with the schlieren. Planar laser-induced fluorescence (PLIF) is one of a variety of planar flow visualization techniques that can provide three-dimensionally spatially-resolved off-body visualizations of boundary layers 5,6,7 and other hypersonic flow phenomena.…”
Section: Introductionmentioning
confidence: 99%